PERANCANGAN BELT CONVEYOR KAPASITAS 30 TON/JAM UNTUK ALAT ANGKUT KERTAS - Dadi Cahyadi; Gilang Febri Azis (University of Muhammadiyah Jakarta, 2015)
This plan aims to produce design and construction working drawings belt conveyor capacity 30 tons/hour in PT. Interact Corpindo as aids paper conveyance strong, sturdy, safe, and efficient so that the mobility of paper products can be run smoothly and efficiently. Conveyor Belt design process capacity of 30 tons/hour in PT. Interact Corpindo is conducted in stages, namely planning and explanation of the task/function, planning product concept (working drawings). Analysis techniques include analysis belt, idler roller, roller conveyor, motor power, the moment that occurs at the input and output shafts, gears and bearings. Conveyor Belt driving force Capacity 30 tons/hour in PT. Interact Corpindo planned to use the motor gearbox that is adapted to the results of the planning and design of 15 kW with a conveyor belt speed from 0.8 to 2 m/s. The results of the design produce a belt width of 800 mm, with a path length of 50 m.